Profile of Courses and Training Institutions (LKP) Amani House of Learning in Batam City - Nabilah Rabbani; MHD Natsir (Universitas Negeri Padang, 2023)
The background of this research is the unique phenomenon that exists at the Amani Learning House Course and Training Institute (LKP) Work training programs at this Institute which have programs located in the garment and embroidery and fashion sectors, especially in the Riau Archipelago and also work together with the Empowerment Service Women, the Office of Manpower who always trust the Institute and provide the most complete facilities and infrastructure when they want to conduct training. The purpose of this study is to find out how the Amani Learning House Course and Training Institute (LKP) Management in Batam City. This research uses a qualitative approach, with a case study research method. The sources of data in this study were managers, tutors and 5 residents studying at the Amani Learning House Course and Training Institute. The data collection techniques used in this study were observation, interviews and documentation. The analysis of intestinal marking is data reduction, data presentation and conclusions. Data validation techniques using the triangulation method, the triangulation principle and triangulation theory. The results of this study indicate (1) in the extracurricular planning component, briefings are carried out before each activity (2) the form of organization in this extracurricular is by grouping forums in each field, namely groups that are not yet able to sew, groups that are able to sew, groups that are able to sew but are not able to use tools (3) in the movement component that the Manager is currently carrying out is by giving indirect directions to learning residents who are attending training courses sew this. However, the Manager usually emphasizes to the learning residents to be serious in practicing in their respective groups, because they are a team that is highly valued for its cohesiveness and interrelatedness. The movements made are mostly from tutors and administrators. (4) direct supervision of learning residents who take part in this sewing course training. This is due to the busyness experienced by the Manager himself, the Manager gives directions to tutors and tutors who will provide direct supervision to the learning residents. Keywords: Management of the Amani Learning House Course and Training Institute (LKP).